Recrystallization of Commercial Carbamazepine Samples-A Strategy to Control Dissolution Variability - Felicia Flicker; Veronika A. Eberle; Gabriele Betz (MDPI AG, 2012)
Physical properties of commercial carbamazepine (CBZ) samples can significantly influence drug release and thereby jeopardize bioequivalence of the final dosage form. The aim of this study was to reduce variability in commercial CBZ samples by recrystallization. CBZ samples of four different suppliers were recrystallized in ethanol solution containing 1% polyvinylpyrrolidone (PVP). CBZ samples were analyzed by disk intrinsic dissolution rate (DIDR), X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), and scanning electron microscopy (SEM). Recrystallized CBZ samples showed strongly reduced variability in DIDR compared to the untreated CBZ samples. Moreover, transformation process to CBZ dihydrate was inhibited; no dihydrate crystals were visible on compact surfaces after 8 h intrinsic dissolution measurement. Recrystallized CBZ samples showed no change in polymorphic form, however, particle size and shape was inhomogenous. In binary mixtures with microcrystalline cellulose, recrystallized CBZ samples again showed difference in drug release. This difference was associated with the inhomogenous particle size in the recrystallized CBZ samples. The results show that a controlled grinding step is required after recrystallization. We suggest the recrystallization in presence of 1% PVP followed by a controlled grinding step as a strategy to reduce dissolution variability in commercial CBZ samples.